Translated Christianities : Nahuatl and Maya religious texts - Christensen, Mark Z. (Latin American originals ;, 2014)
"English translations of Nahuatl and Maya religious texts, including sermons, catechisms, and confessional manuals. Includes commentary examining the various Christianities presented to the colonial Aztec (Nahua) and Yucatec Maya, the origins and purpose of the texts, and their authors and the messages they intended to convey"--Provided by publisher